Study of Various Image Noises and Their Behavior - Kushwaha, Sumit; Singh, Rabindra Kumar (International Journal of Computer Sciences and Engineering, 2015)
Noises in image is a random variation of color and brightness information produced by the sensor and circuitary of a scanner, or digital camera, or transmission of images. Noise can degrade the visual quality of the image. Due to this, we lost so many information from the image. Image Denoising means to restore the noisy image in original form and extract the maximum information as much as possible. In this paper, we studied the various types of noises in the image, how its behavior, with some parameters, with the help of PDF functions using MATLAB.